The Application of User Experience Questionnaire to Evaluate Customer Experience When Using Digital Platform to Purchase Flight Ticket in Two Travel and Ticketing Digital Companies - Sudirjo, Frans; Damara Gugat, Rudy Max; Budi Utama, Ahmad Nur; Utami, Eva Yuniarti; Martis, Andi (SEULANGA SYSTEM PUBLISHER, 2023)
This research aims to find out the results of the assessment and comparison of user experience in online airline ticket booking applications using the user experience questionnaire (UEQ). Data collection methods include using literature studies and distributing questionnaires. The sampling technique used in this research was a simple random sampling method with a total of 100 respondents. Validity tests and reliability tests are also carried out using statistical calculations and tools. Based on the average score assessment on each travel A and travel B application scale using the UEQ questionnaire, both applications have a good overall user experience (UX) level. In travel application A, the average score for each scale, such as attractiveness, is 2.6, clarity is 2.4, efficiency is 2.5, accuracy is 2.4, stimulation is 2.5, and novelty is 2.5, all of which indicate that this application scored above or at least equal to the established